Selection of materials for marine instruments - Ravindran, K., Gopalakrishna Pillai, A.G. and (Fishery Technology, 2021)
The paper describes the selection of materials for the reliable operation of oceanographic instruments. For selecting the material, raft immersion tests were carried out for one year. Results of the tests are presented. Comparisons between metals were discussed.